Avaliação radiomorfométrica da cortical mandibular de brasileiros da região de Ribeirão Preto-São Paulo - Alonso, Maria Beatriz Carrazzone Cal, 1986- (2011)
Orientador: Plauto Christopher Aranha Watanabe